Development and application of neural stem cells for treating various human neurological diseases in animal models - Yi, Bo-Rim (Korean Association for Laboratory Animal Science, 2013)
Stem cells derived from adult tissues or the inner cell mass (ICM) of embryos in the mammalian blastocyst (BL) stage are capable of self-renewal and have remarkable potential for undergoing lineage-specific differentiation under in vitro culturing conditions. In particular, neural stem cells (NSCs) that self-renew and differentiate into major cell types of the brain exist in the developing and adult central nervous system (CNS). The exact function and distribution of NSCs has been assessed, and they represent an interesting population that includes astrocytes, oligodendrocytes, and neurons. Many researchers have demonstrated functional recovery in animal models of various neurological diseases such as stroke, Parkinson's disease (PD), brain tumors, and metastatic tumors. The safety and efficacy of stem cell-based therapies (SCTs) are also being evaluated in humans. The therapeutic efficacy of NSCs has been shown in the brain disorder-induced animal models, and animal models may be well established to perform the test before clinical stage. Taken together, data from the literature have indicated that therapeutic NSCs may be useful for selectively treating diverse types of human brain diseases without incurring adverse effects.